Gelatin/Na2Ti3O7 Nanocomposite Scaffolds: Mechanical Properties and Characterization for Tissue Engineering Applications - Rittichai Sangkatip; Kaona Jongwuttanaruk; Wipoo Sriseubsai (My University, 2023)
Materials and manufacturing technologies are necessary for tissue engineering and developing temporary artificial extracellular matrices. In this study, scaffolds were fabricated from freshly synthesized titanate (Na2Ti3O7) and its precursor titanium dioxide and their properties were investigated. The scaffolds with improved properties were then mixed with gelatin to form a scaffold material using the freeze-drying technique. To determine the optimal composition for the compression test of the nanocomposite scaffold, a mixture design with three factors of gelatin, titanate, and deionized water was used. Then, the scaffold microstructures were examined by scanning electron microscopy (SEM) to determine the porosity of the nanocomposite scaffolds. The scaffolds were fabricated as a nanocomposite and determined their compressive modulus values. The results showed that the porosity of the gelatin/Na2Ti3O7 nanocomposite scaffolds ranged from 67% to 85%. When the mixing ratio was 100:0, the degree of swelling was 22.98%. The highest swelling ratio of 85.43% was obtained when the freeze-drying technique was applied to the mixture of gelatin and Na2Ti3O7 with a mixing ratio of 80:20. The specimens formed (gelatin:titanate = 80:20) exhibited a compressive modulus of 30.57 kPa. The sample with a composition of 15.10% gelatin, 2% Na2Ti3O7, and 82.9% DI water, processed by the mixture design technique, showed the highest yield of 30.57 kPa in the compression test.
Keywords: Gelatin; Bone Tissue Engineering Materials